Resilience in the face of adversity in adults with an intellectual disability: A literature review - Scheffers, Femke (J Appl Res Intellect Disabil, 2020)
BACKGROUND: Persons with an intellectual disability are at a higher risk of experiencing adversities. The concept of resilience offers promising insights into facilitating personal growth after adversity. The current study aims at providing an overview of the current research on resilience and the way this can contribute to quality of life in people with intellectual disability. METHOD: A literature review was conducted in the databases PsycINFO and Web of Science. To evaluate the quality of the studies, the Mixed Method Appraisal Tool (MMAT) was used. RESULTS: The themes, autonomy, self‐acceptance and physical health, were identified as internal sources of resilience. External sources of resilience can be found within the social network and daily activities. CONCLUSION: The current overview shows promising results to address resilience in adults with intellectual disability. More research is needed to identify the full range of resiliency factors.